2003
DOI: 10.1128/jb.185.8.2673-2679.2003
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Properties of RpoS (σ S ) Mutants of Escherichia coli with Postulated N-Terminal Subregion 1.1 or C-Terminal Region 4 Deleted

Abstract: Derivatives of the stationary-phase sigma factor σS of Escherichia coli lacking either of two conserved domains, the postulated N-terminal subregion 1.1 or the C-terminal region 4, were shown to be competent in vitro for transcription initiation from several σS-dependent promoters on supercoiled DNA templates. Unlike wild-type σS, however, the deletion derivatives were inactive on relaxed templates. The anomalous slow electrophoretic mobility of σS on denaturing gels was corrected by deletion of subregion 1.1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 48 publications
(85 reference statements)
0
18
0
Order By: Relevance
“…2B, Shine-Dalgarno sequence [SD]). Translational reinitiation within the E. coli rpoS gene has also been reported previously (15). To facilitate characterization of the rpoS T2 allele in isogenic backgrounds, the rpoS gene from S. Typhimurium ATCC 14028 was replaced by rpoS T2 , yielding strain 2922KrpoS T2 .…”
Section: Resultsmentioning
confidence: 57%
“…2B, Shine-Dalgarno sequence [SD]). Translational reinitiation within the E. coli rpoS gene has also been reported previously (15). To facilitate characterization of the rpoS T2 allele in isogenic backgrounds, the rpoS gene from S. Typhimurium ATCC 14028 was replaced by rpoS T2 , yielding strain 2922KrpoS T2 .…”
Section: Resultsmentioning
confidence: 57%
“…This would explain why s s activity is retained in suppressor-free strains carrying the amber 33 codon. Indeed, a fragment of s s (rpoSD1-53) lacking the first 53 amino acids is functional in vivo (Subbarayan and Sarkar, 2004) as has previously been shown for a fragment lacking the postulated N-terminal subregion 1.1 (Rajkumari and Gowrishankar, 2002;Gowrishankar et al, 2003). Thus, uncertainties surrounding the ancestral sequence of the rpoS gene, the genetic relationships between different K-12 strains, and the strong selective pressures these strains have encountered in the laboratory, make it difficult to draw conclusions about how common down-mutations (or up-mutations) in rpoS are in the real world outside the laboratory.…”
Section: Resultsmentioning
confidence: 65%
“…On the other hand, rpoS from a virulent Salmonella strain (ATCC 14028s) has an ATG start (50). Since it has recently been found that N-terminal deletions of rpoS may retain substantial function (17,36), we tested the function of the S. enterica TTG initiation codon. Site-directed mutations changing the start codon were substituted at the native rpoS locus in the bacterial chromosome as described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%